Publications by faculty members indexed in Science Citation Index and Scopus: an Iranian case study. Issue 6 (6th November 2017) - Galyani-Moghaddam, Golnessa; Jafari, Hassan; Sattarzadeh, Asghar
Abstract : Purpose: The paper aims to report an investigation that was conducted to identify the scholarly publications by faculty members of the Allameh Tabataba'i University that were indexed in two international databases, Science Citation Index (SCI) and Scopus, from the year the databases first included Iranian-authored papers (1987 and 1989, respectively) through the end of 2015. Design methodology/approach: Scientometric methods and social network analysis techniques were used to conduct the study and to analyze the co-authorship network. Both quantitative and qualitative analyses were carried out on the data. Quantitative analysis was accomplished using Microsoft Excel, while the qualitative analysis was carried out using HistCite, VOSviewer and Pajek software. Findings: Faculty members had the most international cooperation with colleagues from the USA and Switzerland, and they jointly authored papers with faculty and staff from other universities within Iran. The three institutions with the highest rate of co-authorship included the Islamic Azad University, Tehran University and Amir Kabir University of Technology. Practical implications: The overall overlap among the two databases was about 21 per cent. The number of papers indexed by Scopus (583 records) was more than that by SCI (410 records). The total number of papers at an international level was much lower than that at the national level (6, 426 records) in both the databases. Originality/value: This paper provides insight into the scholarly works by the faculty of Allameh Tabataba'i University indexed in two international databases, SCI and Scopus. It also examines the co-authorship network structure.